NMR in the epoxidation of (E,E)-Cinnamylideneacetophenones - Santos, Clementina M.M. (2011)
The epoxidation of cinnamylideneacetophenones have been already performed with hydrogen peroxide as an oxidant in Julia's method [1] and with dimethyldioxirane [2], however no studies were performed using salen Mn(III) complexes as catalysts.